Methicillin-resistant Staphylococcus aureus (MRSA) on dispensing counters of community pharmacies in Klang Valley - Yao-Li Chow; Hong-Wai Tham (Progress in Microbes and Molecular Biology)
Staphylococcus aureus has been causing contamination and infection in the hospital and community settings. Methicillin-resistant Staphylococcus aureus (MRSA) was first discovered in the 1960s and epidemics of MRSA were reported soon after the usage of methicillin. The incidence rate of MRSA infections has been increasing for the past 50 years, and community-associated infection may be slowly replacing hospital-associated MRSA strains. This study aimed to investigate the prevalence of MRSA on the dispensing counters of community pharmacies under different settings - community pharmacies in shopping malls and high streets in Klang Valley. With verbal consent, swab samples were collected from dispensing counters of 23 community pharmacies using sterile cotton buds moistened with sterile sodium chloride (NaCl) solution. Samples were spread on nutrient agars and Brilliance MRSA 2 selection agars and incubated at 37ºC. The numbers of colony were documented and statistically analysed using Microsoft Excel and Statistical Package for the Social Sciences (SPSS) Statistics. The results showed that the prevalence of MRSA on the dispensing counters was 22% (5 out of 23), and the difference in MRSA contamination between community pharmacies in shopping mall and high street setting was insignificant (p > 0.05). This study serves as the pioneer study of its kind in Klang Valley. All healthcare professionals and individuals are strongly advised to practise a good level of hygiene to avoid MRSA cross contamination.